2020
DOI: 10.1103/physreva.101.012340
|View full text |Cite
|
Sign up to set email alerts
|

Channel capacity enhancement with indefinite causal order

Abstract: Classical communication capacity of a channel can be enhanced either through a device called a 'quantum switch' or by putting the channel in a quantum superposition. The gains in the two cases, although different, have their origin in the use of a quantum resource, but is it the same resource? Here this question is explored through simulating large sets of random channels. We find that quantum superposition always provides an advantage, while the quantum switch does not: it can either increase or decrease comm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 28 publications
4
55
0
Order By: Relevance
“…In a recent study [51] related to [8], a comparable effect is observed with no indefinite causal order, but instead with a coherent control to determine which of the two depolarizing channels is traversed. These are two distinct phenomena, which can be observed separately as in [8] and in [51], and which are further discussed in [52,11]. The effects for estimation in our study occur in the presence of coherent control of indefinite causal order, as in [8].…”
Section: Discussionmentioning
confidence: 56%
“…In a recent study [51] related to [8], a comparable effect is observed with no indefinite causal order, but instead with a coherent control to determine which of the two depolarizing channels is traversed. These are two distinct phenomena, which can be observed separately as in [8] and in [51], and which are further discussed in [52,11]. The effects for estimation in our study occur in the presence of coherent control of indefinite causal order, as in [8].…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, a related recent result has also shown that, for certain choices of noisy channels, the quantum switch can enable perfect quantum communication, but that this impossible with our setup [52]. Understanding when the quantum switch or the coherent control of channels is a more powerful communication resource [39], as well as the role of indefinite causal order in communication advantages provided by the quantum switch [41], are crucial questions that remain the be fully answered.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, one may intuitively expect the target system to be less "degraded" in the scenario considered here. However, a recent paper exploring numerically this issue [39] (which appeared subsequent to an earlier preprint of this manuscript and, in part, in response to the very questions we raise) indicates that the situation is more subtle, with the noncommutativity of the Kraus operators of the two channels placed inside a quantum switch also playing a role in these communication advantages. In particular, in some cases the quantum switch indeed outperforms coherent control meaning this intuition-at least applied naively-is incorrect, although further study is needed to understand fully the situation.…”
Section: A3 Examplesmentioning
confidence: 93%
See 1 more Smart Citation
“…A typical and striking benefit is when the two channels (1) and ( 2) are two completely depolarizing quantum channels, which are therefore individually incapable of transmitting any useful information. It has then been shown that when two such channels are associated into a switched channel with indefinite order [3,7], or into a coherently superposed channel [4,7], in each scheme effective information communication becomes possible. Comparison has been performed and discussed [4,7,8] to better appreciate the mechanisms and specificities of the two schemes, and the respective roles of indefinite order and of coherent superposition, particularly in reaching similar capabilities of information communication through depolarizing channels.…”
Section: Introductionmentioning
confidence: 99%